Efficacy of PET-CT in the prediction of metastatic adrenal masses that are detected on follow-up of the patients with prior nonadrenal malignancy: A nationwide multicenter case–control study. Issue 34 (26th August 2022) - Arikan, Akif Enes; Makay, Ozer; Teksoz, Serkan; Vatansever, Safa; Alptekin, Hüsnü; Albeniz, Gürcan; Demir, Ali; Ozpek, Adnan; Tunca, Fatih
Abstract : Metastasis is the second most common type of adrenal gland mass. In patients undergoing follow-up for nonadrenal malignancy, adrenalectomy is performed when metastasis to adrenal gland is suspected on the basis of positron emission tomography–computed tomography (PET-CT) imaging. This study investigated the efficacy of PET-CT in the discrimination of metastatic lesions from nonmetastatic lesions in the adrenal glands. In this multicentric study, data was collected from enrolled centers. Forty-one patients who underwent surgery for suspected adrenal metastases were evaluated retrospectively. The following data types were collected: demographic, primary tumor, maximum standardized uptake value of adrenal mass (a-SUVx) and detectability in computed tomography and/or magnetic resonance imaging, and specimen size and histopathology. Six patients were excluded due to unavailability of PET-CT reports and 4 for being primary adrenal malignancy. The rest were divided into 2 groups (metastatic: n = 17, 55% and nonmetastatic: n = 14, 45%) according to histopathology reports. There was no statistical difference between the analyzed values, except the a-SUVx ( P < .05). The a-SUVx cutoff value was defined as 5.50 by receiver operating characteristic curves and compared with literature. There was no statistical difference when each group was divided as low and high ( P > .05). It was found that PET-CT was able to discriminate metastatic lesions from primary benign lesions ( P = .022). PET-CT can discriminate primary benign lesions and metastatic lesions by cutoff 5.5 value for a-SUVx.